Characteristics and outcomes among lung transplant patients with respiratory syncytial virus infection. Issue 4 (22nd June 2021) - Mahan, Luke D.; Points, April; Mohanka, Manish R.; Bollineni, Srinivas; Joerns, John; Kaza, Vaidehi; La Hoz, Ricardo M.; Gao, Ang; Zhang, Song; Torres, Fernando; Banga, Amit
Abstract: Background: To describe characteristics and outcomes among lung transplantation (LT) patients with respiratory syncytial virus (RSV) infection and elucidate the predictors of 1‐year survival after RSV infection. Methods: This was a retrospective chart review study among LT patients with RSV infection between 2013 and 2018 (90 episodes among 87 patients; mean age 56.3 ± 13.1 years, M:F 52:35). A contemporaneous control group consisting of LT patients without RSV infection (n = 183) was included. One‐year survival after the RSV infection was the primary endpoint. Results: Median time from LT to RSV infection was 30 (1‐155) months. Before RSV infection, the median decline in forced vital capacity (FVC) was 9.7 cc (−17.8 to 83 cc) or 0.29% (−1.4% to 4.6%) per month, while the forced expiratory volume (FEV1 ) decline was 7.5 cc (−8.8 to 58 cc) or 0.3% (−0.57% to 4.3%) per month with no statistically significant change after RSV infection. One‐year survival among patients with RSV infection was 86.2% (75/87). Pre‐infection diagnosis of chronic lung allograft dysfunction (CLAD; adjusted HR: 4.29, 1.08‐17.0; P = .038) and FVC or FEV1 decline >10% during 6 months post infection (adjusted HR: 35.1, 3.26‐377.1; P = .003) were independently associated with worse survival. On propensity score matched analysis, RSV infection was not associated with worse post‐transplant survival (HR with 95% CI: 0.79, 0.47‐1.34; P = .38). Conclusions: A majority of LT patients in the current cohort did not experience an alteration in the trajectory of FVC or FEV1 decline after developing RSV infection, and their post‐transplant survival was not adversely impacted. Established CLAD at the time of RSV infection and post infection >10% decline in FVC or FEV1 are independently associated with worse survival after RSV infection.